Modelos Universitarios y Gobierno Corporativo. Trayectorias del capitalismo académico - Salazar J., Mauro (2023)
The essay develops a description of the corporate and business criteria crystallized in the thesis of «corporate governance» embraced by the Anglo-Saxon academy from the deregulation of the Welfare State. Soon the new management will have effects in the Latin American University having a new paradigm linked to the rational choice. The latter, which gradually affected the European States in the second half of the 1970, returns “governance models” that integrate new organizational forms between public worlds, private spheres and mixed figures of tertiary education. Under this context, governance breaks out, whose transition to corporate governance responds to innovations in management, administration and optimization of production within the post-Fordist regime. This process stimulated the participation of non-state actors in the emerging «glonacal university» (global, national and local). The material decline of the regime of «modern knowledge», will be the condition for intensifying a tertiary offer centered on the rise of academic capitalism, once the university of the tax exchequers and the managerial episteme, has become hegemonic in Latin América.